Copper–catalyzed activation of molecular oxygen for oxidative destruction of acetaminophen: The mechanism and superoxide-mediated cycling of copper species. (January 2017) - Zhang, Yunfei; Fan, Jinhong; Yang, Bo; Huang, Wutao; Ma, Luming
Abstract: In this study, the commercial zero-valent copper (ZVC) was investigated to activate the molecular oxygen (O2 ) for the degradation of acetaminophen (ACT). 50 mg/L ACT could be completely decomposed within 4 h in the ZVC/air system at initial pH 3.0. The H2 O2, hydroxyl radical (OH) and superoxide anion radical (O2 − ) were identified as the main reactive oxygen species (ROSs) generated in the above reaction; however, only OH caused the decomposition and mineralization of ACT in the copper-catalyzed O2 activation process. In addition, the in-situ generated Cu + from ZVC dissolution not only activated O2 to produce H2 O2, but also initiated the decomposition of H2 O2 to generate OH. Meanwhile, the H2 O2 could also be partly decomposed into O2 −, which served as a mediator for copper cycling by reduction of Cu 2+ to Cu + in the ZVC/air system. Therefore, OH could be continuously generated; and then ACT was effectively degraded. Additionally, the effect of solution pH and the dosage of ZVC were also investigated. As a result, this study indicated the key behavior of the O2 − during Cu–catalyzed activation of O2, which further improved the understanding of O2 activation mechanism by zero-valent metals. Graphical abstract: Highlights: The ZVC/air system was effective in degradation of ACT. The Cu + was responsible for activation of O2 to produce H2 O2 . The O2 − was formed via the decomposition of H2 O2 in the ZVC/air system. It was proved that the O2 − mediated the copper cycling by reduction of Cu 2+ to Cu + .